2015
DOI: 10.3892/ijo.2015.3192
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced modulation of immunogenic genes in tumor cells is regulated by both histone deacetylases and DNA methyltransferases

Abstract: Abstract. Radiation treatment is a pivotal therapy for several cancer types, including colorectal cancer. It has been shown that sublethal doses of radiation modulate gene expression, making tumor cells more susceptible to T-cell-mediated immune attack. We have recently shown that low dose radiation enhances expression of multiple death receptors (Fas, DR4 and DR5) and co-stimulatory molecules (4-1BBL and OX-40L) in colorectal cancer (CRC) cells; however, it is unclear how ionizing radiation (IR) enhances expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…Demethylation of the foxp3 locus yields the gene accessible to the binding of numerous transcription factors [62]. Radiation can alter the epigenetic enzymes associated with specific gene promotors in cancer cells [63,64] and has been reported to alter DNA methylation, both globally and in a gene-specific manner [65]. Thus, it seems reasonable that radiation could be altering the epigenetic state of the foxp3 locus, and we would expect iT REGS to be more sensitive to these changes since the region is already partially methylated.…”
Section: Discussionmentioning
confidence: 99%
“…Demethylation of the foxp3 locus yields the gene accessible to the binding of numerous transcription factors [62]. Radiation can alter the epigenetic enzymes associated with specific gene promotors in cancer cells [63,64] and has been reported to alter DNA methylation, both globally and in a gene-specific manner [65]. Thus, it seems reasonable that radiation could be altering the epigenetic state of the foxp3 locus, and we would expect iT REGS to be more sensitive to these changes since the region is already partially methylated.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have reported that radiation (5 Gy) similarly increases histone acetylation at both the Fas and DR5 promoters in addition to the 4-1BBL promoter. Further, less HDAC2, HDAC3 and DNMT1 were bound to the promoter regions of both 4-1BBL and Fas, but not other genes following IR of human tumor cells [77]. These observations suggest that radiation can also regulate the expression of specific genes by epigenetic mechanisms.…”
Section: Epigeneticmentioning
confidence: 79%
“…DNMTs are responsible for methylating DNA and for silencing genes. We have recently observed that 4‐1BBL expression is regulated by DNA methylation in colorectal cancer cells (Cacan et al, ). However, it is unclear if suppression of 4‐1BBL and OX‐40L are regulated by DNA methylation in chemoresistant ovarian cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recruitment of DNA methyltransferases (DNMTs) and histone deacetylases (HDACs) to the promoter region of a gene suppresses its transcriptional activity. It has been shown that expression of OX‐40L and 4‐1BBL can be influenced by DNA methylation and histone acetylation in colorectal cancer (Cacan et al, ). Thus, epigenetic regulation of costimulatory molecules may also contribute to their dynamic expressions in cancer progression; however, the molecular details about epigenetic regulation of these costimulatory molecules in chemoresistant ovarian cancer cells remain unknown.…”
Section: Introductionmentioning
confidence: 99%